2021
DOI: 10.1101/2021.05.18.444646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of common mutations in the SARS-CoV-2 Spike RBD domain and its ligand the human ACE2 receptor on binding affinity and kinetics

Abstract: The interaction between the SARS-CoV-2 virus Spike protein receptor binding domain (RBD) and the ACE2 cell surface protein is required for viral infection of cells. Mutations in the RBD domain are present in SARS-CoV-2 variants of concern that have emerged independently worldwide. For example, the more transmissible B.1.1.7 lineage has a mutation (N501Y) in its Spike RBD domain that enhances binding to ACE2. There are also ACE2 alleles in humans with mutations in the RBD binding site. Here we perform a detaile… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 51 publications
(106 reference statements)
0
23
0
Order By: Relevance
“…Similarly, p.Ser19Pro also does not introduce any new Spike contacts according to the mCSM-PPI2 model and so the enhanced affinity is difficult to explain but it is has been suggested that the Pro mutant stabilises the helix to favour Spike interaction 22 . ACE2 p.Ser19Pro is of further interest because of its proximity to Spike Ser477, which has mutated to Asn in circulating SARS-CoV-2 strains and these ACE2 and RBD variants have been found to interact 28 . The mCSM-PPI2 structural models of the p.Asp355Asn, p.Glu37Lys and p.Gly352Val were discussed in detail in our previous work 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, p.Ser19Pro also does not introduce any new Spike contacts according to the mCSM-PPI2 model and so the enhanced affinity is difficult to explain but it is has been suggested that the Pro mutant stabilises the helix to favour Spike interaction 22 . ACE2 p.Ser19Pro is of further interest because of its proximity to Spike Ser477, which has mutated to Asn in circulating SARS-CoV-2 strains and these ACE2 and RBD variants have been found to interact 28 . The mCSM-PPI2 structural models of the p.Asp355Asn, p.Glu37Lys and p.Gly352Val were discussed in detail in our previous work 23 .…”
Section: Resultsmentioning
confidence: 99%
“…As the most exposed region, the RBD is targeted by approximately 90% of the nABs in COVID-19 convalescent sera and has been subject to multiple mutations that contribute to human adaption, viral fitness and immune escape [40][41][42][43][44][45][46][47][48]. A key mutation that is shared by the Alpha, Beta, Gamma, Theta, Mu and C.1.2 variants is N501Y, which contributes to a substantial transmission advantage of these variants mediated by increased binding affinity to the ACE2 receptor [18,[49][50][51][52][53][54][55][56][57][58]. However, studies using sera of BNT162b2-immunized patients demonstrated no reduced susceptibility to the neutralization of S proteins with only the N501Y SNP [59,60].…”
Section: Origin and Evolution Of Sars-cov-2 In Humansmentioning
confidence: 99%
“…However, studies using sera of BNT162b2-immunized patients demonstrated no reduced susceptibility to the neutralization of S proteins with only the N501Y SNP [59,60]. Additional mutations in the RBD with high global prevalence are N439K, L452Q, S477N and E484K, which also enhance ACE2 binding and, in case of N439K, increase viral loads [56][57][58]61]. The substitution K417N/T, present in the Beta and Gamma variants, is reported to reduce the receptor interaction by disruption of a salt bridge formed by K417 with D30 in ACE2 [56,57].…”
Section: Origin and Evolution Of Sars-cov-2 In Humansmentioning
confidence: 99%
See 2 more Smart Citations